Study of lipid profiles high and normal body mass index in polycystic ovary syndrome women in Aljouf, Saudi Arabia - Salma, Umme; Alshaikh, Ahmed Baker A.; Alanazi, Muhannad Faleh; Sheikh, M. Sayed Ali; Rashwan, Eman K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: For women of reproductive age, polycystic ovary syndrome (PCOS) is the most prevalent endocrinological condition. Hyperandrogenism, persistent ovulatory dysfunction, obesity, and insulin resistance have all been associated with PCOS. However, recently PCOS is detected in high-body weight and normal-body-weight women. No information was available to evaluate specific lipid profiles. The goal of this study is to analyze the lipid profiles of women with polycystic ovarian syndrome who have high or normal body weight. Methods: This polycystic ovarian syndrome (PCOS) retrospective study was carried out between January 2021 and January 2022 at Sakaka’s Maternity and Children Hospital (MCH), Aljouf, Saudi Arabia. A total of 68 PCOS women were included in the study; we divided them into high (n=34) and normal body weight (n=34) according to the calculation of BMI. We obtain the test results of lipid profiles and demographic data from hospital record files. Results: We noticed changes but no significance in our research of lipid profiles in high and normal PCOS participants. The CHOL, TG, HDL, and LDL, 159.30±4.193, 97.89±7.140, 60.91±9.564, and 99.47±9.22 shown in the high BMI PCOS women respectively. While, 129.28±3.702, 83.69±4.49, 46.84±1.68 and86.53±4.36 were detected in normal BMI PCOS women respectively. There were none that were statistically significant, with the exception of cholesterol p=0.001. Conclusions: Our results show that POCS women with normal body weight and PCOS women with high BMI have different changes in their lipid profiles, but no significance has been found other than higher cholesterol levels. Therefore, losing weight can stop lipid profiles from altering, which may reduce difficulties in the future.